Assessing management costs and tenant outcomes in social housing: recommended methods and future directions - Pawson, H.; Milligan, V.; Liu, E.; Phibbs, P.; Rowley, Steven (Australian Housing and Urban Research Insttitute, 2015)
There is a consensus expectation that agencies providing public services mandated by governments should operate in a transparent, contestable and accountable way. Quantifying service performance is, therefore, a fundamental requirement for service provider agencies. In the social housing field, the past 20 years has seen a growing emphasis on the measurement of service outcomes as well as inputs and outputs. In this realm, such outcomes measures are usually derived from surveys or from administrative records. In Australia, social housing outcomes monitoring is substantially reliant on the two-yearly National Social Housing Survey that continues to provide a widely-respected benchmark on tenant satisfaction. However, there are a number of respects in which the survey could be enhanced. A key outcome indicator shedding light on social landlord effectiveness on social inclusion is the measurement of tenancy sustainment. To improve its utility, this measure could be more precisely targeted, as well as being extended to encompass community housing providers as well as public housing providers. A broad brush indication of landlord cost-effectiveness may be derived by relating an individual provider's tenant satisfaction ratings to its unit management expenditure and this is exemplified through our research. However, there are numerous qualifications that would need to be attached to any such assessment and, as illustrated in our working through of case study landlord data, these would include the questionable comparability of satisfaction statistics derived through non-standard survey methodologies. Case study fieldwork confirmed support for the contention that measures of tenancy sustainment can be a useful indicator of social landlord effectiveness in regards to social inclusion, and that the existing measure applicable to public housing providers could and should be extended to larger CHPs. However, while there is widespread acceptance for the logic of more precisely targeting tenancy sustainment monitoring to focus on 'at risk' tenants, there is no consensus on how 'at risk' might be specifically defined for these purposes. Similarly, while the logic of our proposed measure of 'economic re-connection' was again generally acknowledged, it was clear that the feasibility of such a metric would depend on utilisation of Centrelink records. Our survey of 429 tenants recently housed by two case study providers confirmed that a move into social housing was usually associated with 'positive changes' in tenants' lives. These included, that most respondents rated their new home as superior to their former dwelling, as well as indicating that the new 'home neighbourhood' tended to be seen as preferable to the applicant's former locality-especially in terms of 'safety' and 'friendliness'. However, less than a quarter rated their new landlord as 'helpful' in terms of aiding new tenants to address nonhousing issues (e.g. making links with other agencies as required). Similarly, only a very small proportion (2%) reported that a stronger engagement with employment (since being housed) was associated with any direct assistance from their housing provider. Moreover, the proportion of recently housed tenants reportedly 'working more' than prior to being housed in social housing (7%) was lower than the proportion working less in the current tenancy than previously (20%). This apparently paradoxical finding is likely to be partly a product of the way that access to social housing is prioritised according to 'need'. Thus, the onset of sudden need, such as disability or the imminence of a birth, while also being associated with a condition negatively impacting on the tenant's 'employability' might have materially contributed to a household's priority for a tenancy offer. This highlights the challenge inherent in attempting to gauge social landlords' success in economic reconnection and the necessity for targeting any such metric on those deemed 'work capable'.